Evaluation of DNA single and double strand breaks in women with cervical neoplasia based on alkaline and neutral comet assay techniques - Cortés Gutiérrez, Elva I.; Hernández Garza, Fernando; García Pérez, Jorge O.; Dávila Rodríguez, Martha I.; Aguado Barrera, Miguel E.; Cerda Flores, Ricardo M. (John Wiley & Sons, 2012)
A hospital-based unmatched case-control study was performed in order to determine the relation of DNA single (ssb) and double (dsb) strand breaks in women with and without cervical neoplasia. Cervical epithelial cells of 30 women: 10 with low grade squamous intraepithelial lesions (LG-SIL), 10 with high-grade SIL (HG-SIL), and 10 without cervical lesions were evaluated using alkaline and neutral comet assays. A significant increase in global DNA damage (ssb + dsb) and dsb was observed in patients with HG-SIL (48.90 ± 12.87 and 23.50 ± 13.91), patients with LG-SIL (33.60 ± 14.96 and 11.20 ± 5.71), and controls (21.70 ± 11.87 and 5.30 ± 5.38; resp.). Pearson correlation coefficient revealed a strong relation between the levels ssb and dsb (r2 = 0.99, P = 0.03, and r2 = 0.94, P = 0.16, resp.) and progression of neoplasia. The increase of dsb damage in patients with HG-SIL was confirmed by DNA breakage detection-FISH (DBD-FISH) on neutral comets. Our results argue in favor of a real genomic instability in women with cervical neoplasia, which was strengthened by our finding of a higher proportion of DNA dsb.